Notas sobre el manejo del software geoestadístico Variowin. Parte I: Cálculo del variograma - Santamaría, Mariana S. (2006)
The term Geostatistics covers the analysis and modeling of spatial data that are distributed in a coordinate system of space and/or time. The theory of the regionalized variable, or Geostatistics, was born as an inference methodology to evaluate ore reserves and extended rapidly to other spatial observations where basic assumptions of classical statistics did not work. The three basic steps in a geostatistical study include: exploratory data analysis, structural analysis (calculation and modeling of variograms) and making predictions (kriging or simulations). This paper aims to provide a detailed introduction to the exploration and calculation of variograms using Variowin 2.21 software package. This packages is freely available from internet. Modeling of variograms is detailed in a another paper (Part II). This software Variowin is designed to make it easy for the novice to begin using geostatistical methods, as well as to provide sufficient power and flexibility for the experienced user to solve real-world problems.